Take it from me...a print public service announcement campaign against drunk driving - Herrera, Juan Carlos Miguel N.
In October 2008, I became a statistic- a victim of a vehicular accident caused by driving under the influence of alcohol. Drunk driving has been a perennial problem, almost everyday we hear on the news or read about it in the newspapers ? people getting hurt, properties damaged and even lives lost because of the deadly mix of alcohol and driving. Using my own experience with driving under the influence of alcohol, I decided to study Public Service Announcement campaign -especially posters, and the visual elements used in creating these posters. The study was then used to create my own PSA campaign using my experience as the central theme of the campaign. The campaign was not only designed to raise awareness against drunk driving, it was also designed in such way that it will tell my experience.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts